A comparative analysis of biologics market dynamics in 12 countries: (Bio)similar and sustainability - Song, Younghyun; Shin, Gyeongseon; Choi, Gyeyoung; Han, Euna; Ou, Huang-tz; Bae, SeungJin (Frontiers in Pharmacology, 2025)
ObjectiveWe sought to evaluate the relationship between biosimilar introduction and the prices and expenditures of biologics in high-income countries.MethodsThis study examined IQVIA-MIDAS sales data for biologics and biosimilars from January 2018 to June 2020 across 12 high-income countries (Australia, Austria, Canada, France, Germany, Italy, Japan, Korea, Spain, Sweden, Switzerland, and the United Kingdom). We selected seven biologics that fall under the World Health Organization Anatomical Therapeutic Chemical code L (Antineoplastic and immunomodulating agents), and categorized them into two groups based on the availability of biosimilar data. Group A consisted of biologics with biosimilars-etanercept, infliximab, rituximab, and trastuzumab, while Group B comprised biologics without biosimilars, including cetuximab, nivolumab, and pembrolizumab. A descriptive analysis was conducted to investigate the association between biosimilar introduction and trends in Fisher price index and relative expenditure. In addition, two-sample t-test and Wilcoxon rank-sum test were used to assess the statistical significance of differences in growth rates between the two groups.ResultsGroup A exhibited a declining trend in the Fisher price index, whereas Group B remained stable across most countries, with average compound quarterly growth rates being −2.19% and −0.54%, respectively (p < 0.001). Relative expenditure trends also revealed contrasting patterns between the groups across most countries, further highlighting the differences. The average compound quarterly growth rates for relative expenditures was −1.78% for Group A and 7.66% for Group B (p < 0.001).ConclusionThe introduction of biosimilars was significantly associated with reductions in the prices and expenditures of biologics in high-income countries. This underscores the potential role of biosimilars in supporting the long-term sustainability of the healthcare system.